The cool table—limiting warm ischaemia in fillet-of-leg free flap harvest: a case series - Oliver Miles; Eldon Mah (Australasian Journal of Plastic Surgery)
The amputated part is an ideal donor for sarcoma defect reconstruction in proximal lower limb amputation; however, these composite tissues are at risk of tissue ischaemia during long operations. A retrospective case investigation of four patients receiving fillet-of-leg flaps for proximal lower limb and pelvis sarcoma reconstruction was performed. A ‘cool table’ was used for fillet-of-leg harvest from the amputated part to limit warm ischaemia. Three flaps were myocutaneous, the other osseomyocutaneous including tibia. Ischaemia time ranged between 75 and 150 minutes. All flaps survived with no vascular complications.